PENGEMBANGAN LKPD INTERAKTIF BERBASIS LIVEWORKSHEETS PADA MATA PELAJARAN IPAS KELAS V DI SDN 2 SIGERONGAN - Safitri, Dian; Asrin; Hasnawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The suboptimal use of interactive media in science education at SDN 2 Sigerongan has led to students being less engaged in the learning process. This study aims to develop an interactive student worksheet based on Liveworksheets for the fifth-grade IPAS subject at SDN 2 Sigerongan that is valid and practical for use in learning. This research employed the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. The subjects of this study were 24 fifth-grade students of SDN 2 Sigerongan. The instruments used included validation questionnaires for media and material experts, as well as response questionnaires for teachers and students. The results showed that the interactive LKPD based on Liveworksheets obtained a validity percentage of 91% from media experts (very valid) and 91% from material experts (very valid), with an overall average of 91% (very valid). The practicality test results indicated that the teacher response reached 92%  while student responses in individual, small group, and large group trials were 91,33%, 91,67%, and 91,87%, respectively, all categorized as very practical. Therefore, the developed Liveworksheets-based interactive LKPD is considered valid and highly practical, making it suitable for use as a learning medium in elementary school IPAS subjects.